(untitled) (Research, Society and Development, 2021)
The hiring of startups follows a basic rite, but with peculiar nuances, being the signing of a letter of intent, followed by the signing of a confidentiality agreement, later the audit process and, finally, the signing of the investment term. In this perspective, this article, through exploratory research, of a qualitative nature, deductive method, collection of bibliographic-documental data, proceeded in order to carry out an analysis on contracts within the scope of startups as a way of providing a foundation and encouraging activities performed in the sphere of startups, especially with regard to legal security and economic growth. In addition, it is worth pointing out the horizontality of the fundamental norms of the Brazilian legal system, thus, the relationship between investor and startup-investee must also respect the axiological load. Finally, in view of the exposed problem, it was sought, based on corporate legal instruments, to elucidate the need for businessmen, based on legal security and respect for economic growth, to seek to use legal instruments as a form of economic promotion.